Fire Chief commenting on Team Trinity designs firefighter uniform prototype - Eisele, John, photographer (Colorado State University. Libraries, 2016)
Alan Fletcher, Fire Chief Fairmount Fire Protection District, Golden, Colorado.
The 2016 Fairmount Fire Rescue Fire Department Uniform Design was held at the Gifford Building, Colorado State University.
AM375.
SP2016 AM375 Firefighter Uniform Redesign.
Keywords: Fire departments -- Uniforms -- Design -- Awards; Fashion design -- Awards